Utilización de proteína de origen animal en dietas para ovinos criollos mejorados, en etapa de engorde - Cardenas Aguilar, Andryk Jeffry (2019)
This thesis report on the "Use of protein of animal origin in diets for improved creole sheep, in the fattening stage" carried out in the VAQUIA SAC stable, with the aim of determining the effect of the use of protein of animal origin in diets for improved creole sheep, in the fattening stage, the same ones that were distributed in the pens according to the treatments, in each pen there were 33 sheep, the Completely Random Design (DCA) was used with a total number of two treatments: T0 (Control): 0%, T1 (With protein of animal origin): 2.5%, and 33 repetitions. The protein of animal origin was included in the food respectively, in the T1 treatment. The initial weight (kg), feed consumption, final weight (kg) were recorded and the variables were evaluated as weight gain, feed conversion, mortality, benefit-cost ratio. The results obtained showed that the T1 treatment obtained a significant difference compared to the T0 with a differential weight gain at 30 days, and at 45 days it was 4.00 Kg average weight, likewise the T1 obtained an improvement in body condition. Regarding the feed conversion, it was obtained that the T1 sheep that were supplied with concentrate containing the protein of animal origin, showed the best feed conversion (8.45) compared to the T0 treatment. In conclusion, by supplying protein of animal origin, we will obtain good and better results in terms of production parameters, body condition, weight gain and the benefit-cost ratio.